Studies on the Influence of Altitude on Abundance of Fall Armyworm (Spodoptera Frugiperda (JE Smith)) (Lepidoptera: Noctuidae) in Tanzania - Mbemba, Kiva F.; Rwegasira, Gration M.; Tryphone, George M. (Discoveries in Agriculture and Food Sciences, 2023)
Fall armyworm (FAW) (Spodoptera frugiperda) is one of the most devastating polyphagous field crop pests in many parts of the world, including Tanzania. Influence of altitude on the abundance of S. frugiperda was studies by using Pheromone (Frugilure S. frugiperda, Chemtica international, S.A) embedded cup traps. The study was conducted along sites of Mt. Uluguru slopes including; SUA (525 masl), Mlali (579 masl), Mgeta (1050 masl) and Nyandira (1691 masl) located in Morogoro Region, Tanzania. A total of 16 cup traps (four at each site equidistantly arranged at 100 m apart) were used. Weather data were recorded using Hygrocron i-button hung on a tree at equidistant from the four traps. Data on S. frugiperda counts and weather variables were recorded weekly for duration of six months from January to June 2020. Results showed that S. frugiperda was abundantly recorded across he tested altitude albeit at varied abundance. There was significant difference (p < 0.001) among altitude on S. frugiperda abundance, whereby at low altitude, S. frugiperda abundance was high compared to medium and high altitude. Rainfall had positive correlation on S. frugiperda abundance (r = 0.16, r = 0.04) for SUA and Mlali and negative correlation (r = -0.44) and (r = -0.03) for Mgeta and Nyandira. Temperature had positive correlation (r = 0.21) on S. frugiperda abundance at Nyandira while SUA (r = -0.03), Mlali (r = -0.35) and Mgeta (r = -0.28) had negative correlation. Relative humidity for all four locations showed negative correlation with S. frugiperda abundance. Thus, appropriate and effective management practices of S. frugiperda should be considered throughout maize production areas and across crop production seasons regardless of the altitude.